Tobias S. Buckell's Galactic Caribbean Future. Issue 1 (1st January 2015) - DeGraw, Sharon
Abstract : Caribbean writer Tobias S. Buckell has created a futuristic galaxy in which Afro-Caribbeans take center stage. In his first two novels, Crystal Rain (2006) and Ragamuffin (2007), Buckell describes the world of New Anegada and its environs, establishing the Xenowealth series. New Anegada resembles the Caribbean in population, topography, language, and culture. In the colonization of New Anegada, the galactic African diaspora comes into conflict with aliens, the Asian-inspired Hongguo, and a "native" population known as the Azteca. The historical white colonizer is elided, and people of color occupy every major role in both texts. In Crystal Rain and Ragamuffin, Buckell offers an alternate, positive model of race consciousness which reflects the greater inclusion of postcolonial writers in science fiction (sf). Buckell utilizes science fiction to signify on historical colonialism and race relations, while simultaneously emphasizing a contemporary postcolonial reality.